Self-Development of Dance at SMAN 1 Coastal Realm South Coastal District - Suci, Suci Silvia Ningsih; Herlinda Mansyur (Universitas Negeri Padang, 2024)
This study aims to reveal and describe the process of implementing dance self-development at SMAN 1 Ranah Pesisir Kabupaten Pesisir Selatan. This type of research is qualitative research with descriptive methods of analysis. The research instrument is the researcher himself and is assisted by supporting tools such as stationery and cameras. Data were collected through observation techniques, interviews, literature studies, and documentation. The analyzing steps are carried out through data collection, data reduction, data presentation and data verification. The results showed that the self-development of dance at SMAN 1 Ranah Pesisir Kabupaten Pesisir Selatan was carried out through the planning, implementation and evaluation stages. Planning is carried out through collaboration between the Principal, Student Representatives and Guidance teachers so that self-development can be carried out conducively. The implementation of dance self-development activities is carried out outside school class hours. Evaluations are conducted by principals, student representatives, coaches/trainers conducted in midterm exams. In its implementation, the self-development of dance has been going well. Supporting factors in the implementation of dance self-development are (availability of facilities and infrastructure as support in dance self-development activities. While the inhibiting factor in this dance self-development activity is the absence of student dance bases so that students are slow to understand the movements given. However, these inhibiting factors can be overcome by the coach with the drill practice method, which is an exercise by repeating the movements given so that students can do the movements and make groups so that they can learn with their friends.